Effect of water saturation on the electrical properties of cement and alkali-activated slag composites with graphite conductive admixture. (26th December 2022) - Rovnaník, Pavel; Kusák, Ivo; Bayer, Patrik
Highlights: Electrical resistivity significantly increases with decreasing moisture level, especially when the saturation degree drops below 30%. The resistivity of cement-based material at zero moisture level is approximately ten times higher in comparison with alkali-activated slag. Composites with graphite content above the percolation threshold show no influence of moisture on the electrical properties. Influence of the electrical resistivity on the water saturation degree can be fitted using a sigmoidal regression function. Abstract: This study investigated the influence of water saturation degree on the electrical properties of two different types of building materials – Portland cement and alkali-activated slag mortars with graphite powder as a conductive admixture. The graphite content ranged between 0 and 18 wt% of the cement/slag in order to cover the area below as well as above the percolation threshold. The properties were tested in terms of electrical resistivity measurement with an AC-frequency in the range of 40 Hz – 1 MHz, and the results were correlated with meso -scale structural changes evaluated by means of mercury intrusion porosimetry and scanning electron microscopy. The electrical resistivity of both materials decreased with increasing AC-source frequency and increasing water saturation degree. In a dry state, alkali-activated slag exhibited approximately ten times lower resistivity than cement-based material. The addition of graphite gradually decreased the resistivity until the percolation threshold was reached, but no influence of moisture on the resistivity was observed at dosages exceeding 12 wt% of graphite. The dependence of electrical resistivity on the water saturation degree was fitted for two different frequencies (50 Hz and 1 kHz) using a sigmoidal regression function.